2022
DOI: 10.1109/lra.2022.3144767
|View full text |Cite
|
Sign up to set email alerts
|

Passive Inverse Dynamics Control Using a Global Energy Tank for Torque-Controlled Humanoid Robots in Multi-Contact

Abstract: This work presents a passivity-based inverse dynamics (ID) controller using a global energy tank. The proposed control approach allows us to achieve a safe multi-contact scenario on a torque controlled humanoid robot. The controller is primarily a task space ID quadratic programming (QP) which efficiently computes the reference torque satisfying a non-hierarchical set of tasks. Our work extends this controller by adding a global energy tank modulating the task gains, with power regulation, to ensure the passiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…The force value 15 N was chosen based on an initial investigation which has shown that a screw tightened with 3 Nm needs approximately 15-20 N of force applied to avoid slippage. The maximum energy threshold E total was selected according to ISO/TS 15066:2016 [29] that specified a range of 0.52 -2.5 J, the value for P motion and the threshold for the power limit on the energy tank P tank were picked according to earlier results in [17], [18] and in [24], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The force value 15 N was chosen based on an initial investigation which has shown that a screw tightened with 3 Nm needs approximately 15-20 N of force applied to avoid slippage. The maximum energy threshold E total was selected according to ISO/TS 15066:2016 [29] that specified a range of 0.52 -2.5 J, the value for P motion and the threshold for the power limit on the energy tank P tank were picked according to earlier results in [17], [18] and in [24], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…where I u is the n 3 n generalized inertia matrix, and H u is the convective inertia matrix as given in equations ( 29) to (30), respectively…”
Section: Robot Modellingmentioning
confidence: 99%
“…Their introduction into industries, such as health care, with complex interactive behaviour has revealed the limitations of traditional industrial controllers. The impedance controller [1][2][3][4][5][6] is a widespread technique enabling robots to interact with uncertain environments. This control technique relies on inverse dynamics modelling to drive the robot to act with a desired mechanical impedance, such as a linear Mass-Spring-Damper system [1,7].…”
Section: Introductionmentioning
confidence: 99%
“…Examples are environments that require adaptive trajectories and/or variable impedance gains [8], as well as tasks with uncertain end-effector contact against other agents or the environment (e.g., polishing, physical human-robot collaboration, etc.) [3][4][5][6][9][10][11][12][13]. Such tasks pose various challenges to robots' controllers that currently require an accurate model of contact conditions to ensure system stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation